PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA ULAK PATIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU TAHUN 2020 - Atika Fadilla; Sofyan Hadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The financial governance of the Ulak Patian Village Government, Kepenuhan District, Rokan Hulu Regency in carrying out village financial management must be in accordance with the principles of good governance in village financial management and the stages of planning, budgeting, implementation, administration, reporting, and accountability, and coaching, supervision. This is done in order to create good financial governance. The problem in this research is that planning and budgeting are not in accordance with the needs of the community, in terms of implementation it has also not been able to realize the budget and does not prioritize important programs with existing finances, this is also due to the lack of human resources in Ulak Patian Village. The purpose of this study was to find out and to analyze the perceptions of village government apparatus based on the principles of good governance with the dimensions of transparency, accountability and capacity participation of village apparatus on the performance of village fund management. The approach in this research is descriptive. The research location was conducted in Ulak Patin Village, Kepuhan District, Rokan Hulu Regency, using data collection techniques through interviews and documentation. The results of the study showed that financial management in Ulak Patian Village, Kefulan District, Rokan Hulu Regency was not optimal. Judging from the planning, it has not set a priority scale, so that the community's needs are not met. In terms of implementation, it has not realized all that was planned. Then the reporting and accountability have not been carried out in a timely manner, this is due to the lack of quality human resources. This is because the HR already knows and understands what will be done properly so that the presentation of financial reporting can be timely. Quality financial reports should not be made by just anyone. The people who make these financial reports must be people who are truly experts in their field. Keywords: Participation,Transparency,Accountability, SDM